2013
DOI: 10.1002/lary.24354
|View full text |Cite
|
Sign up to set email alerts
|

Is type 2 diabetes mellitus associated with alterations in hearing? A systematic review and meta‐analysis

Abstract: Type 2 diabetic patients had significantly higher incidence for at least the mild degree of HL when compared with controls. Mean PTA thresholds were greater in diabetics for all frequencies but were more clinically relevant at 6000 and 8000 Hz. Prolonged ABR wave V latencies in the diabetic group suggest retro-cochlear involvement. Age and duration of DM play important roles in the occurrence of DM-related HL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
92
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 66 publications
17
92
2
1
Order By: Relevance
“…When comparing previous NL-SH results on hearing and comorbid conditions [Stam et al, 2014] with the current results, the present findings confirm the association between hearing impairment and diabetes. The data seem to further strengthen the evidence that exists for the association between hearing loss and diabetes as outlined in two recently published review studies [Horikawa et al, 2013;Akinpelu et al, 2014]. In these two review studies it was suggested that in patients with diabetes histological changes occur in the basilar membrane and stria vascularis leading to hearing loss.…”
Section: Main Findings and Previous Researchsupporting
confidence: 57%
See 1 more Smart Citation
“…When comparing previous NL-SH results on hearing and comorbid conditions [Stam et al, 2014] with the current results, the present findings confirm the association between hearing impairment and diabetes. The data seem to further strengthen the evidence that exists for the association between hearing loss and diabetes as outlined in two recently published review studies [Horikawa et al, 2013;Akinpelu et al, 2014]. In these two review studies it was suggested that in patients with diabetes histological changes occur in the basilar membrane and stria vascularis leading to hearing loss.…”
Section: Main Findings and Previous Researchsupporting
confidence: 57%
“…Relationships are reported between reduced hearing and diabetes [Horikawa et al, 2013;Akinpelu et al, 2014], cardiovas-nantly focused on the potential ototoxic effects of medication on hearing. It is known that several types of medicines can damage the inner ear temporarily or permanently [Van Eyken et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies exploring the direct association between atherogenic risk factors and hearing loss show inconsistent findings: dyslipidemia in terms of elevated levels of total cholesterol, low-density lipoprotein (LDL), triglycerides (TG) and low levels of high-density lipoprotein (HDL) have shown mainly adverse effects on hearing ability [Gates et al, 1993;Suzuki et al, 2000;Shargorodsky et al, 2010] but a gainful effect of high total cholesterol level has also been reported [Jones and Davis, 2000]. A relation between hearing ability and diabetes-related measures has been reported in several studies [Austin et al, 2009;Jang et al, 2011;Akinpelu et al, 2014], which is also the case for smoking [Fransen et al, 2008;Shargorodsky et al, 2010] and high BMI [Fransen et al, 2008;Lalwani et al, 2013]. Other studies, however, have shown conflicting results for these factors [Gates et al, 1993;Shargorodsky et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…More recent population-based epidemiological studies (e.g., Bainbridge, Cheng, & Cowie, 2010;Bainbridge, Hoffman, & Cowie, 2008;Dalton, Cruickshanks, Klein, Klein, & Wiley, 1998) and systematic reviews or meta-analyses (Akinpelu, Mujica-Mota, & Daniel, 2014;Horikawa et al, 2013) support increased prevalence and incidence of hearing loss among adults with type 2 diabetes, although the strength of this association tended to weaken with advancing age. The systematic review and meta-analysis by Akinpelu et al (2014) also observed prolonged auditory brainstem response Wave V latencies among diabetics, suggesting an impact on higher level auditory processing. Konrad-Martin et al (2016), in a study of 222 older veterans, about half with type 2 diabetes and half without, found significantly longer latencies for cortical auditory evoked potentials, especially the P2 component.…”
mentioning
confidence: 99%